2011
DOI: 10.1073/pnas.1012351108
|View full text |Cite
|
Sign up to set email alerts
|

RNAi screen of the protein kinome identifies checkpoint kinase 1 (CHK1) as a therapeutic target in neuroblastoma

Abstract: Neuroblastoma is a childhood cancer that is often fatal despite intense multimodality therapy. In an effort to identify therapeutic targets for this disease, we performed a comprehensive loss-offunction screen of the protein kinome. Thirty kinases showed significant cellular cytotoxicity when depleted, with loss of the cell cycle checkpoint kinase 1 (CHK1/CHEK1) being the most potent. CHK1 mRNA expression was higher in MYC-Neuroblastoma-related (MYCN)-amplified (P < 0.0001) and high-risk (P = 0.03) tumors. Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
229
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(253 citation statements)
references
References 32 publications
21
229
1
Order By: Relevance
“…[22][23][24][25][26] In contrast to the well-known utility of Chk1 inhibitors in sensitizing tumors to chemotherapy agents, 23,27,28 Chk1 overexpression or downexpression also occurs in some types of tumors, including breast cancer, ovarian cancer, cervical cancer, and neuroblastoma. 22,[29][30][31][32][33] In our study, we found Chk1 mRNA and protein levels were upregulated in colorectal cancer tissues compared with paired normal tissues, and positively correlated with CCNB1 expression. We hypothesized that CCNB1 might serve as a Chk1-induced oncogene in colorectal cancer.…”
Section: Discussionsupporting
confidence: 49%
“…[22][23][24][25][26] In contrast to the well-known utility of Chk1 inhibitors in sensitizing tumors to chemotherapy agents, 23,27,28 Chk1 overexpression or downexpression also occurs in some types of tumors, including breast cancer, ovarian cancer, cervical cancer, and neuroblastoma. 22,[29][30][31][32][33] In our study, we found Chk1 mRNA and protein levels were upregulated in colorectal cancer tissues compared with paired normal tissues, and positively correlated with CCNB1 expression. We hypothesized that CCNB1 might serve as a Chk1-induced oncogene in colorectal cancer.…”
Section: Discussionsupporting
confidence: 49%
“…High p-CHK1 expression in the nucleus or cytoplasm also significantly correlated with recurring HPV þ tumors. Although this is a small sample set, high CHK1 expression and/or activity has previously been correlated with therapy-resistant cancer cells (35,36) and associated with high-grade, high-risk tumors often resistant to therapy and with a poor prognosis (36)(37)(38)(39)(40). Confirmation of our findings in a larger head and neck cancer dataset will be required.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that RET is required for retinoic acid-induced neuroblastoma differentiation [158], and that RET inhibition is effective in neuroblastoma preclinical models [159]. Other recent studies have identified the polo-like kinase 1 (PLK1) as a potential target for neuroblastoma therapy, based on screens of a library of kinase inhibitors in neuroblastoma preclinical models [160], while a screening study using an siRNA library identified the checkpoint kinase 1 (CHK1) as a potential target [161]. Transcriptome analysis of neuroblastoma tumor formation in the MYCN transgenic mouse model identified the centromereassociated protein E (CENP-E) as an additional potential therapeutic target [162].…”
Section: Treatment -Relapsed and Refractory Neuroblastomamentioning
confidence: 99%